Kitab Futuh el-Sham (Pseudo-) Muhammada ibn Umar al-Waqidi’ego jako źródło do studium bitwy nad rzeką Jarmuk (636) - Matvieiev, Andrii (Vox Patrum, 2021)
This article focuses on the course of the Battle of Yarmouk, which took place on August 20, 636 between the Byzantine army under the command of Vahana and the caliphate forces commanded by Khalіd іbn al-Walid. The source of these analyzes is kitab, whose author is from (Pseudo-) al-Waqidi. It is not about analyzing the purely military aspect of this clash, but about its interpretation in Islamic tradition at the beginning of the 9th century. One of the bearers of this tradition is (Pseudo-) al-Waqidi. The clash over Yarmouk was not only a military defeat of the Byzantine Empire, but a defeat that determined the fate of Syria and Palestine. They came under the rule of the caliphate and never returned to the Empire. Interpreting this event, (Pseudo-) al-Waqidi emphasizes that it was a breakthrough in creating a new order in this part of the world. Moreover, this new order was created thanks to the bravery of Muslim warriors and their wives. Emphasizing the role of women in this victory is particularly noteworthy because Islam usually does not highlight their significance. (Pseudo-) al-Waqidi also points to the fact that in the battle of Yarmouk, the Christian God did not effectively support his followers. Allah did so, which resulted in defeat of the imperial army. The fight over Yarmouk was, therefore, in (Pseudo-) al-Waqidi’s opinion on two levels: human and supernatural. Allah’s followers won a victory in it, which was not only a victory over Christians, but also over the faith. In this sense, the work analyzed here is an important witness to the emergence of an imperial Muslim tradition that combines historical and religious interpretation.